Analysis of Elementary School Teachers’ Ability in Compiling HOTS Questions in Mathematics Subjects - Indahwati, Rohmah; Zumam, Wildona; Harini, Sri; Hasanah, Sri Indriati; Fauziyah, Nur; Basri, Hasan; Magfiroh, Syamsiyatul; Ulum, Asifaul (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Higher Order Thinking Skills (HOTS) is one of the essential competencies that must be developed from an early age because it plays an important role in forming students’ critical and logical thinking skills. However, students’ abilities in this aspect are still low, one of the influencing factors being the limited facilitation of HOTS questions provided by teachers. This study aims to determine: (1) the comparison of HOTS and LOTS questions made by teachers; (2) teachers’ understanding of HOTS questions; and (3) teachers’ difficulties in compiling HOTS questions. This study employed a qualitative research approach with a qualitative case study. The respondents consisted of 6 teachers selected based on certain criteria. Data were obtained through interviews and reviews of daily test documents, with a total of 51 questions analyzed using the revised Bloom’s taxonomy framework. Data analysis referred to Miles and Huberman’s stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the percentage of HOTS questions appearing in teachers’ daily test items was still low. Only 4 out of the 51 analyzed questions (8%) were classified as HOTS questions, while the remaining items were categorized as lower-order thinking skills (LOTS) questions. In addition, only 1 teacher (17%) correctly understood the definition of HOTS questions, while 5 teachers (83%) did not. Teachers also experienced difficulties in developing stimuli and finding references related to HOTS questions. These findings indicate that teachers require structured training in distinguishing procedural application questions (C3) from authentic HOTS tasks at the C4–C6 levels.